Study on lipid and fatty acid composition of Thelenota ananas collected from Bai Dong Island, Ha Long Bay, Vietnam - Dang, Thi Phuong Ly; Dang, Thi Minh Tuyet; Dao, Thi Kim Dung; Nguyen, Thi Nga; Pham, Minh Quan; Pham, Quoc Long (Vietnam Journal of Marine Science and Technology, 2024)
The paper studies the lipid and fatty acid composition of the sea cucumber Thelenota ananas collected on Bai Dong Island, Ha Long Bay, Vietnam. The total lipid content of dry sample weight was relatively high (11.89%). The triacylglycerol TG has the highest concentration in total lipids with a ratio of up to 66.73%; the PL and PI classes do not have a significant difference with the proportions of 13.44 and 11.65% in total lipids. Two classes of sterol ST, hydrocarbon-wax HW and free fatty acid FFA account for a small proportion. The two main classes of phospholipids are PC and PE, with a ratio of 47.10% and 33.29% of total phospholipids. There are 36 fatty acids identified, of which total saturated fatty acids (SFA) account for 41.61%; Monounsaturated fatty acids (MUFA) account for 32.15%, and polyunsaturated fatty acids (PUFA) account for 25.63%; the main fatty acids are stearic acid (18:0) accounting for 13.15% of the total fatty acids; 16:1n-9 accounts for 14.87%, and 20:5n-3 EPA fatty acids account for 15.3% of the total fatty acids. Among the fatty acids, n-9 (omega 9) accounts for the highest proportion with 25.16%; n-3 fatty acids (omega 3) account for 18.43%; n-6 (omega 6), n-7 (omega 7) fatty acids account for 5.8 and 6.5%, respectively. In this study, the n3/n6 ratio of the sea cucumber sample Thelenota ananas was 3.18%, consistent with the evaluation standards of the World Health Organization (WHO) of n3/n6 ratio ≥ 0.1%. It is classified as a good foodstuff for human health; therefore, it can be considered a source of food that can be used to serve community health care needs.